ANALISIS KINERJA PERBANKAN SYARIAH DENGAN PENDEKATAN MAQASHID INDEX DAN SHARIA CONFORMITY AND PROFITABILITY (SCNP) - Nurul Lifa Apriliya; Maslichah Maslichah (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACT                   This study aims to measure the performance of Islamic banking using Maqashid index and the Sharia Conformity and Profitability (SCNP) model. The population this research is Sharia Commercial Bank (BUS) are listed on IDX for the period 2013-2017 using the purposive sampling method. The results  of study show that islamic Commercial Banks which are ranked first, second, third and sixth MSI calculations are ranked fourth, fifth and seventh, the calculation of MSI is in the ULQ. BUS quadrant which is ranked the last is in the LRQ quadrant.Keywords : Islamic Banking, Performance, Maqashid Sharia Index (MSI), Sharia Conformity and Profitability (SCNP) Model, Profitability.